Colicin E3 cleavage of 16S rRNA impairs decoding and accelerates tRNA translocation on Escherichia coli ribosomes. - Lancaster, L; Savelsbergh, A; Kleanthous, K; Wintermeyer, W; Rodnina, M (2008)
The cytotoxin colicin E3 targets the 30S subunit of bacterial ribosomes and specifically cleaves 16S rRNA at the decoding centre, thereby inhibiting translation. Although the cleavage site is well known, it is not clear which step of translation is inhibited. We studied the effects of colicin E3 cleavage on ribosome functions by analysing individual steps of protein synthesis. We find that the cleavage affects predominantly the elongation step. The inhibitory effect of colicin E3 cleavage originates from the accumulation of sequential impaired decoding events, each of which results in low occupancy of the A site and, consequently, decreasing yield of elongating peptide. The accumulation leads to an almost complete halt of translation after reading of a few codons. The cleavage of 16S rRNA does not impair monitoring of codon-anticodon complexes or GTPase activation during elongation-factor Tu-dependent binding of aminoacyl-tRNA, but decreases the stability of the codon-recognition complex and slows down aminoacyl-tRNA accommodation in the A site. The tRNA-mRNA translocation is faster on colicin E3-cleaved than on intact ribosomes and is less sensitive to inhibition by the antibiotic viomycin.